Biological Control of Chromium Redox and Stable Isotope Composition in the Surface Ocean - Janssen, David J. (Global Biogeochem Cycles, 2020)
While chromium stable isotopes (δ(53)Cr) have received significant attention for their utility as a tracer of oxygen availability in the distant geological past, a mechanistic understanding of modern oceanic controls on Cr and δ(53)Cr is still lacking. Here we present total dissolved δ(53)Cr, concentrations of Cr (III) and total dissolved Cr, and net community productivity (NCP) from the North Pacific. Chromium concentrations show surface depletions in waters with elevated NCP, but not in lower productivity waters. Observed Cr deficits correspond well with calculated Cr export derived from NCP and Cr:C ratios of natural phytoplankton and marine particulates. Chromium (III) concentrations are stable over the diel cycle yet correlate with NCP, with maxima found in highly productive surface waters but not in lower productivity waters, indicating biological control on Cr (III). The relationship between Cr (III) and δ(53)Cr suggests that δ(53)Cr distributions may be controlled by the removal of isotopically light Cr (III) at an isotopic enrichment factor (∆(53)Cr) of −1.08‰ ± 0.25 relative to total dissolved δ(53)Cr, in agreement with the global δ(53)Cr‐Cr fractionation factor (−0.82‰ ± 0.05). No perturbation to δ(53)Cr, Cr, or Cr (III) is observed in oxygen‐depleted waters (~10 μmol/kg), suggesting no strong control by O(2) availability, in agreement with other recent studies. Therefore, we propose that biological productivity is the primary control on Cr and δ(53)Cr in the modern ocean. Consequently, δ(53)Cr records in marine sediments may not faithfully record oxygen availability in the Late Quaternary. Instead, our data demonstrate that δ(53)Cr records may be a useful tracer for biological productivity.